Nursing of a patient with severe acute pancreatitis and distributive shock (1例重度急性胰腺炎合并分布性休克患者的护理体会) - ZHANG Yi (张依); SU Ruosi (苏若思); WANG Yutao (王玉涛); WANG Nannan (王楠楠); LIU Yunchao (刘云超); GUO Lian (郭连) (Journal of International Translational Medicine Limited, 2024)
This article summarized the nursing management of a patient with severe acute pancreatitis and distributive shock. Based on the comprehensive nursing risk assessment, an individualized nursing plan was established including fasting management, gastrointestinal decompression, inhibiting pancreatic secretion, Traditional Chinese Medicine enema, Mangxiao external application and targeted interventions on fluid resuscitation and vasoactive agent administration. Integrative nursing interventions are effective to relieve the abdominal pain and improve the early recovery of the patient. (本文总结1例重度急性胰腺炎合并分布性休克患者的护理经验。通过对患者进行综合全面的护理评估, 制定个性化护理计划, 包括禁食、胃肠减压、抑制胰腺分泌、中药灌肠、芒硝外敷等, 并针对液体复苏、血管活性药物的使用等干预措施实施优质护理, 有效缓解患者腹痛, 促进患者早期康复。)